Singapore's Blueprint for Excellence: Crafting a World-Class Education System - Shaturaev, Jakhongir (Unisia, 2024)
This review article explores the remarkable evolution of Singapore's education system, which has been meticulously developed over the past four and a half decades. This system has not only achieved exceptional efficiency but has also garnered global acclaim. A testament to its success is the consistently outstanding performance of Singaporean students in international assessments, in which they frequently outperform their peers from other advanced nations. Singapore's education system is a journey of meticulous crafting from its nascent stages to its current state of excellence. This article examines the various phases of development that have shaped Singapore's educational landscape. A critical aspect of this transformation is the high-quality functioning of educational institutions that are seamlessly integrated into the nation's economic framework. This integration has resulted in an education system that is both compact and robust, thus effectively contributing to Singapore's socioeconomic development. The focal point of this study is the unique administrative and management strategies employed within the Singaporean educational system. These strategies have been instrumental in driving the system towards excellence. The insights presented in this article are drawn from the findings of a 2023 working visit by the administrative delegation of Tashkent State University of Economics to Singapore. Through this visit, the delegation gleaned valuable observations and lessons from Singapore's education model. This article provides a comprehensive analysis of these findings, offering a detailed examination of the elements that constitute Singapore's educational prowess.